Effect of Ovario~hysterectomy on serum enzymatic and hormonal profile in bitches suffering from Pyometra - DABHI, D M; DHAMI, A J; TANK, P H; KELAWALA, N H (The Indian Journal of Animal Reproduction, 2023)
Serum enzyme and hormonal profile was studied in bitches to evaluate it's prognostic and therapeutic signifi.cance. The mean values of serum aspartate aminotransferase (AST) and serum alanine aminotransferase (ALT) were higher (69.43 ± 3.98 and 77.86 ± 7.70 IU/1, respectively) in bitches affected with pyometra as compared to healthy ones (33.60 ± 2.85 and 30.80 ± 1.39 IU/1). However, there was no difference in their profile between closed and open pyometra, and the levelsdrop a little following ovario-hysterectomy in affected animals. The serurri alkaline phosphatase (ALP)activity was also elevated in pyometric bitches than the normal ones (81.14 ± 7.93 vs 40.40 ± 3.87KAU %). Serum total cholesterol concentration in pyometric bitches was significantly higher (P
Keywords: Bitch; Pyometra; Enzymes; Steroids; Ovario-hysterectomy